(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In today’s global context, the concept of sustainable development has evolved from a theoretical proposition to an urgent necessity. The relentless exploitation of natural resources, mounting pollution, and the clear signals of global warming have compelled nations to rethink their industrialization processes. In this regard, the idea of the green industry—the promotion of economic activities and sectors that are environmentally friendly and resource-efficient—has emerged as a promising pathway for countries aspiring for long-term prosperity. The green industry is not only about mitigating the environmental footprints of traditional sectors; it is also about opening new avenues for economic growth that are in harmony with nature. For developing countries like Uzbekistan, the transition to a green industrial model offers opportunities to reconcile economic development with ecological sustainability. This essay provides a comprehensive analysis of the rise of the green industry in Uzbekistan, focusing on its potential, strategies, challenges, and, most importantly, its effect on economic growth.